2014
DOI: 10.1530/ec-14-0039
|View full text |Cite
|
Sign up to set email alerts
|

Variation in the androgen receptor gene exon 1 CAG repeat correlates with manifestations of autoimmunity in women with lupus

Abstract: Clinical and experimental evidence support a role for gonadal steroids in modulating the expression and course of autoimmune diseases such as lupus. Whether or not inherited variation in sensitivity to circulating androgenic hormones could influence the manifestations of such disease is, however, unknown. We sought to determine whether differences in androgen sensitivity conferred by variation in the exon 1 CAG repeat region of the androgen receptor (AR) gene were associated with differences in the clinical or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…In addition, it has been suggested that inflammatory cytokines in affected tissues modulate aromatase activity to locally dampen the effects of androgens in favor of estrogens in lupus patients ( 203 ). Finally, male lupus patients with reduced AR signaling produce higher quantities of IgG autoantibodies ( 204 ), while female lupus patients with the same polymorphism exhibited reduced disease ( 78 ). It is not clear why reduced androgen signaling is associated with opposite effects on lupus in male and female patients.…”
Section: Androgens In Autoimmunitymentioning
confidence: 99%
“…In addition, it has been suggested that inflammatory cytokines in affected tissues modulate aromatase activity to locally dampen the effects of androgens in favor of estrogens in lupus patients ( 203 ). Finally, male lupus patients with reduced AR signaling produce higher quantities of IgG autoantibodies ( 204 ), while female lupus patients with the same polymorphism exhibited reduced disease ( 78 ). It is not clear why reduced androgen signaling is associated with opposite effects on lupus in male and female patients.…”
Section: Androgens In Autoimmunitymentioning
confidence: 99%
“…Moreover, the length of the CAG repeat region in exon 1 of the AR gene influences its signaling activity ( 47 49 ). Studies in men and women with systemic lupus erythematosus (SLE) and rheumatoid arthritis (RA) demonstrated variable and sex dependent effects of this heritable trait on disease severity and phenotype ( 50 53 ).…”
Section: Androgens Signal Through Cytosolic Androgen Receptor (Ar) Anmentioning
confidence: 99%
“…Systemic lupus erythematosus (SLE) affects females 10 times more frequently than males and strikes predominantly during the reproductive years. It also displays an earlier onset of disease and a shortened lifespan in females as compared with males [ 22 ]. Administration of E2, a highly active metabolite of estrogen, accelerates disease onset in females, whereas administration of testosterone ameliorates disease progression [ 22 ].…”
Section: Reviewmentioning
confidence: 99%
“…It also displays an earlier onset of disease and a shortened lifespan in females as compared with males [ 22 ]. Administration of E2, a highly active metabolite of estrogen, accelerates disease onset in females, whereas administration of testosterone ameliorates disease progression [ 22 ]. These studies provided compelling evidence that an alteration in sex hormones levels is one of the factors that might contribute to the predominance of SLE in the female population.…”
Section: Reviewmentioning
confidence: 99%